Strategi Bertahan UMKM bagi Pedagang Kecil di Era Transformasi Digital: Resilience Strategies for Micro, Small, and Medium Enterprises (MSMEs) Among Small-Scale Traders in the Digital Transformation Era - Muhammad Hafizh Sandy Al Fauzan; Tengku Sri Ramadonna; Imelda Suryati Maulani; Aulia Nabila Safitri; Arif Saefudin (Program Studi Tadris Ilmu Pengetahuan Sosial (TIPS) UIN Datokarama Palu, 2025)
This study aims to examine how small traders in the MSME sector use digital transformation as a resilience strategy in adapting to business changes. The research was conducted in Pamulang using a descriptive qualitative approach, involving food and beverage traders who have either adopted or not adopted digital platforms such as social media, marketplaces, and e-wallets. Data were collected through observation, in-depth interviews, and documentation, and analyzed using Miles and Huberman’s interactive model of data reduction, display, and conclusion drawing. The results show that several traders have adopted digital technology, especially non-cash payment systems through QRIS and the use of marketplaces to reach wider markets. However, most consumers still prefer cash due to convenience and habit. Social media promotion is rarely carried out actively by traders, yet often appears organically from customers or influencers. The main factors supporting business sustainability are product quality, direct customer interaction, and strategic business location.